Amalfitano or The Unlimited Wind Rose: the imaginary nation in Los sinsabores del verdadero policía, of Roberto Bolaño (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
The present study attempts to show that through the novel Los sinsabores del verdadero policía (2011), Roberto Bolaño constructs an allegory of the cracks that are caused in the symbolic frame of global geography through the figure of its protagonist, Oscar Amalfitano. From this character in constant transit through other territories, the author shows clearly the diasporic situation of a subject that represents the conflict of individuals who cross borders established in the logic of the map drawn by the West, thus constituting a violation of the configuration of national identity itself. In this approach, the figure of Amalfitano as the subject that deconstructs the Eurocentric idea of wind rose and allows the appropriation of this notion to generate an almost "archimboldiano" game: the origin of the the unlimited wind rose.
Keywords: Nation; identity; cartography; territory; vanishing points